The Silent Woman in the “Criminal Conversation” Trial and her Displaced Defences: “A Letter Always Reaches its Destination” - Smith, Marie (Romanticism on the Net, 2007)
AbstractIn the 18th-19th-century ‘criminal conversation’ legal action, a spouse could sue his wife’s lover for economic compensation. The wife was not party to the action, even though she was implicitly ‘on trial’. This article argues that the absence of the wife’s perspective permitted the court to manipulate her image conservatively and enabled English Marriage Law to evade enlightenment pressure for reform. The counter-pressure she may have exerted is deflected elsewhere. This article shows that women’s private defences could infiltrate the public imagination obliquely, if not the legal process directly, using as examples three very different letters: a purloined love letter from an adulterous wife, a fictional letter of frank testimony from Wollstonecraft’s Maria, and a forensic analysis under a masculine pseudonym from an indignant ‘victim’.